Reduced Equol Production and Gut Microbiota Features in Men With Lean Nonalcoholic Fatty Liver Disease. Issue 4 (August 2022) - Iino, Chikara; Endo, Tetsu; Iino, Kaori; Tateda, Tetsuyuki; Sato, Satoshi; Igarashi, Go; Mikami, Kenichiro; Sakuraba, Hirotake; Yokoyama, Yoshihito; Nakaji, Shigeyuki; Fukuda, Shinsaku
Patients with lean nonalcoholic fatty liver disease (NAFLD) may have different metabolic profiles than those with NAFLD. Estrogenic activity is associated with NAFLD pathogenesis. We evaluated the production ability of equol, which has estrogenic activity, in lean NAFLD and assessed their gut microbiota in relation to their equol-producing ability. Among 684 adult participants, 276 (40%) had NAFLD and 293 (43%) were equol producers. The rates of equol producers in the normal and NAFLD groups were 43% and 42%, respectively. Among the patients with NAFLD, 55 (20%) had lean NAFLD of which 18 (33%) were equol producers. The rate of equol production in men with lean NAFLD was 8%, which was the lowest, while the corresponding rate in the other participants was approximately 40%. The gut microbiota composition of equol producers and nonproducers showed many significant differences. The gut microbiota of men with lean NAFLD showed increased abundance of Caulobacter and decreased abundances of Slackia and Terrisporobacter . Thus, almost all men with lean NAFLD lacked equol-producing ability, and their gut microbiota showed a reduced abundance of Slackia, which is related to equol production. The pathology of lean NAFLD in men may be strongly associated with equol-producing ability and gut microbiota.